Innovation for Whom? A Critical Examination of Equity Gaps in Social Innovation Ecosystems Across Low- and Middle-Income Countries - Suman Thapa; Bina Magar; Anil Bhattarai (Journal of Loomingulisus ja Innovatsioon, 2026)
Social innovation has become an increasingly important strategy for addressing complex development challenges across low- and middle-income countries. Despite substantial investments in collaborative innovation ecosystems, growing evidence suggests that innovation benefits are not distributed equitably among social groups, raising important questions regarding participation, governance, and distributive justice. This study aimed to examine how inclusive governance, stakeholder participation, institutional trust, collaborative networks, organizational learning, and resource accessibility influence distributive equity and social innovation performance across diverse innovation ecosystems. A mixed-methods sequential explanatory research design was employed involving 840 participants from twelve low- and middle-income countries representing governments, universities, civil society organizations, social enterprises, donor agencies, and community organizations. Quantitative data were analyzed using Structural Equation Modeling, while qualitative evidence was collected through semi-structured interviews, focus group discussions, policy analysis, organizational observations, and comparative case studies. Findings revealed that inclusive governance significantly improved distributive equity through enhanced stakeholder participation, collaborative learning, and institutional trust. Collaborative networks strengthened innovation performance; however, unequal access to resources and decision-making opportunities continued to limit meaningful participation among marginalized communities. Results indicate that innovation ecosystems achieve sustainable social impact only when equity is positioned as a fundamental governance principle rather than a secondary policy objective. The study proposes an integrated framework that reframes innovation success through the combined lenses of institutional inclusiveness, distributive justice, and collaborative governance, providing practical guidance for policymakers, development agencies, and innovation practitioners seeking more equitable and sustainable development outcomes.